Patient participation in pro re nata medication in forensic psychiatric care: A nursing document analysis - Hipp Kirsi; Repo-Tiihonen Eila; Kuosmanen Lauri; Katajisto Jouko; Kangasniemi Mari (WILEY, 2025)
Accessible summaryWhat is known on the subjectAs-needed medication is commonly used for psychiatric inpatients' acute psychiatric and physical symptoms. Both patients and staff can initiate such medication.Earlier studies have focused on what and how as-needed medication has been used for psychiatric reasons. Little is known about how patients participate in planning, administration and evaluation of as-needed medication and its alternatives. Nursing documentation provides an insight into these practices.What this paper adds to existing knowledgeLong-term inpatients have an active role in initiating as-needed medication. However, patients and staff may have divergent opinions on the need for medication.Alternatives to medication are mostly proposed by staff, and the feedback on as-needed medication events is usually provided from nurses' point of view.What are the implications for practicePatients' views on decision-making and evaluation should be noticed and documented more.Patient participation can be promoted by planning as-needed medication and its alternatives beforehand.Introduction Pro re nata (PRN) medication is unscheduled and used for acute physical and psychiatric symptoms. Previous studies have focused on the what and how of psychotropic PRN administration. Initiators of PRN events and occasions in which PRN was denied have rarely been studied. Thus, knowledge of patient participation in PRN is fragmented.Aim We aimed to describe and explain long-term psychiatric inpatients' participation in relation to planning and initiation of, as well as decisions and feedback on their PRN medication treatment.Methods We retrieved data from patients' (n = 67) nursing documentation in a Finnish forensic psychiatric hospital in 2018. Data were analysed using statistical methods.Results All patients were prescribed PRN, and they initiated half of the 8,626 PRN events identified, in a 1-year period. Non-pharmacological strategies were rarely (6%) documented, and most of them were initiated by staff (76%). Feedback on PRN was usually from a nurse's viewpoint (71%). Nurses' feedback was positive (80%) more often than patients' (50%).Discussion Patient participation needs to be recognized throughout the PRN process. Future research could continue to explore patient participation in planning and evaluating their PRN medication.Implications for practice Patients participate in PRN by requesting medication. Their participation can be developed by supporting patients to communicate their choice of non-pharmacological methods, take the initiative for medication when needed and disclose their viewpoint on the effects of PRN.